Prevalence and Correlates of Microalbuminuria in Children with Sickle Cell Anaemia: Experience in a Tertiary Health Facility in Enugu, Nigeria - Christopher Bismarck Eke; Henrietta Uche Okafor; Bede Chidozie Ibe (International Journal of Nephrology)
Microalbuminuria is a pre-clinical marker of renal damage in children with sickle cell anaemia and can predict renal failure. Reported prevalence rates increased with age. In Nigeria, burden of disease and prevailing poor health facilities necessitate its screening, determination of prevalence and associated risk factors. It is a cross-sectional as well as descriptive study. Screening microalbuminuria used subjects’ early morning urine. Socio-demographic as well as clinical details were ascertained using semi-structured questionnaires and case files. Associations and statistical relationship of prevalence rates and clinical/epidemiological data were ascertained using chi-squared and multivariate analysis . Two hundred children with sickle cell anaemia (4–17 years) in steady state and 200 age/gender-matched controls were enrolled. Prevalence of microalbuminuria was ,respectively, 18.5% and 2.5% for subjects and controls . Microalbuminuria was commoner in females (19.8%) than males (17.4%) , increased with age , significantly associated with haemoglobin level and hospitalizations (0.001). Subjects had normal renal function. Hospitalizations and haemoglobin levels showed statistical significance on multivariate analysis. Prevalence of microalbuminuria is 18.5%. Age, haemoglobin concentrations, and higher hospitalizations influenced microalbuminuria among subjects. Screening for microalbuminuria should be incorporated in the case management of subjects with identified risk factors.